2018
DOI: 10.11613/bm.2018.030901
|View full text |Cite
|
Sign up to set email alerts
|

Biotin and high-sensitivity cardiac troponin T assay

Abstract: IntroductionThe high-sensitivity cardiac troponin T assay of Roche Diagnostics is known to have interference with high concentrations of biotin as this assay uses biotin-streptavidin binding as detection method. As studies so far have not shown if different biotin concentrations could have diverse influence on various troponin concentrations and whether interference could be removed by available protocol within corresponding turnaround time we aimed to investigate it.Materials and methodsPlasma samples were sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…However, these analytes comprise only a fraction of the ones in this study, and shorter incubation times should be evaluated for all concerned assays before they are applied to minimize the increase in turnaround times even further. Schrapp et al 33 described that the interference in troponin T hs is independent of initial troponin concentrations, an observation that we also made in most tested competitive and sandwich immunoassays, with the exception of NT-proBNP. Trambas et al, 2 on the other hand, found the interference of biotin caused proportional changes in sandwich immunoassays regardless of initial analyte concentrations, whereas competitive immunoassays showed a particularly exaggerated positive bias in samples with low analyte concentrations.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…However, these analytes comprise only a fraction of the ones in this study, and shorter incubation times should be evaluated for all concerned assays before they are applied to minimize the increase in turnaround times even further. Schrapp et al 33 described that the interference in troponin T hs is independent of initial troponin concentrations, an observation that we also made in most tested competitive and sandwich immunoassays, with the exception of NT-proBNP. Trambas et al, 2 on the other hand, found the interference of biotin caused proportional changes in sandwich immunoassays regardless of initial analyte concentrations, whereas competitive immunoassays showed a particularly exaggerated positive bias in samples with low analyte concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…The adsorption caused an increase in the CVs and analytical imprecision in all tested assays, with the exception of cortisol, FT3, NT-proBNP, and procalcitonin, when compared with the manufacturer-supplied CVs in a comparable parameter range (Tables 2 and 3). Schrapp et al 33 made the same observation in their evaluation of biotin depletion in the Elecsys assay for troponin T hs. The increased CVs should not be problematic in most analytes, with the exception of troponin T hs and HIV.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations